Edaphic rather than climatic controls over 13C enrichment between soil and vegetation in alpine grasslands on the Tibetan Plateau. (10th January 2015) - Yang, Yuanhe; Ji, Chengjun; Chen, Leiyi; Ding, Jinzhi; Cheng, Xiaoli; Robinson, David; Whitehead, David
Summary Soil organic carbon (SOC) dynamics is crucial for evaluating ecosystem carbon balance and its feedback to climate warming. However, it is difficult to detect statistically significant changes in SOC stock over short‐time period due to its large pool size, slow turnover time and huge spatial heterogeneity. Stable isotopic measurements, such as Δ δ13C (i.e. the difference of natural abundance of 13C and 12C (δ13C) between surface soils and source plants) and its variations along environmental gradients provide an alternative approach inferring soil carbon dynamics over broad geographical scale. However, current isotopic evidence is primarily derived from temperate and tropical regions, with very limited measurements available in alpine regions. Here, we examined spatial variations of Δ δ13C in alpine grasslands on the Tibetan Plateau, using large‐scale isotopic measurements obtained from consecutive field samplings. We aimed to test whether previously observed isotopic patterns in temperate and tropical regions still hold true in alpine regions and whether climatic or edaphic variables regulated large‐scale patterns of 13C enrichment between soil and vegetation in alpine ecosystems. Our results showed that topsoil stable carbon isotope composition in alpine steppe and meadow ranged from −26·1‰ to −19·7‰ and from −25·7‰ to −22·2‰, with an average of −23·7‰ and −24·1‰, respectively. As previously observed in temperate forests, soil δ13C exhibited linear increases with plant δ13C in alpine grasslands. In contrast to earlier findings, our results revealed that edaphic rather than climatic factors regulated spatial variability of the Δ δ13C in high‐altitude regions. Moreover, edaphic controls over Δ δ13C exhibited meaningful differences between alpine steppe and meadow. The Δ δ13C exhibited an initial increase and a subsequent decrease with soil carbon content in alpine steppe, but was negatively associated with silt content and carbon: nitrogen ratio in alpine meadow. Our results confirmed the association between the δ13C of surface soils and vegetation across contrasting ecosystems, but revealed that edaphic rather than climatic variables were better explanations of 13C enrichment between soil and vegetation at high altitudes. Changes in soil texture and substrate quality could therefore induce soil carbon dynamics in alpine ecosystems.